Caracterização de tipo e raça de populações do nematóide de cisto da soja detectadas no município de Jataí/GO e proximidades por hospedeiros diferenciadores - Figueiredo, Adriana (2008)
The soybean is the most important oleaginous in production under extensive cultivation in Brazil occupying the second position of world production. Alongside the expansion of soybeans culture in Brazil, there was also an increase in plant health problems, including that of the soybean cyst nematode, (NCS), Heterodera glycines Ichinohe, 1952. The classification of the fhytoparasitos and particularly in the NCS races, or biotypes pathotypes using a reliable system is crucial to the search for resistant cultivars. Therefore, the knowledge of the genetic diversity of NCS in a particular region, it is necessary to direct the improvement programme obtain resistant genotypes. This work was aimed at the characterization of races and types of NCS the council of Jataí/GO by differentiators hosts. The test was conducted in a greenhouse in a completely randomized design following the factorial 10x9 (10 hosts differentiators of nematode populations x 9) and six repetitions. The sowing of the hosts differentiators and cultivars used as a pattern of susceptibility and resistance occurred in boxes of kept in BOD for 5 days at 25 °C until the issuance of roots system. The transplant was done to plastic tubes filled with a mixture of soil + sand, in the proportion of 1:2, previously fumigated with methyl bromide for. The inoculum was prepared from each of the 9 populations of the NCS from the municipality of Jataí/GO through the centrifuge technique of fluctuation in solution of sucrose and was calibrated to contain 4000 eggs of H. glycines in 10 mL. The assessment of the population (number of cysts in the soil in the root + females) occurred 35 days after inoculation. The reactions of the differentiators hosts were determined based on the rate of females (IF), which was calculated from the ratio of the average number of females and/or cysts recovered at the differential host and the average number of females and/or cysts in cultivating Lee 74 , multiplied by 100. The IF was used to characterize the race and type. The results show that from 9 populations of the NCS from the region of Jataí/GO were found to 4 different races (3, 5, 6 and 15) and 6 types (0, 2.7, 2.3.5.7, 5.7, 6 e 7). The presence of more than one race or type shows that there will be greater difficulty in obtaining cultivars resistant to the nematode to manage infested areas.